Integrasi Nilai Islam dalam Etika Profesi Kedokteran: Kajian Literatur Kesehatan Islami - Nisa', Salwaa Kaamilatun; Sakuntala Laksono, Raden Roro Niramaya; Setiawan, Moch Ardin; Winayah, Mesri Ananta (Maliki Interdisciplinary Journal, 2025)
Medical ethics is a set of moral guidelines that govern the behavior of healthcare professionals when providing services to patients.s In the context of Islam, medical ethics is not only based on professionalism and medical knowledge, but also comes from spiritual values found in the Quran and Hadith. This study aims to understand the ethical codes that healthcare workers should follow and how they align with Islamic teachings. The research method used is a literature review by examining various scientific sources, both national and international, that discuss medical ethics principles and Islamic moral values. The findings show that medical ethics is based on four main moral principles: autonomy (respecting the patient's rights), beneficence (doing good), non-maleficence (avoiding harm), and justice (fairness). From an Islamic perspective, these principles align with the maqashid syariah, which is to protect religion, life, intellect, lineage, and property. Islamic medical ethics emphasizes sincere intention, responsibility, honesty, and compassion in serving patients. A Muslim doctor is seen not only as a medical practitioner but also as a servant of God and a vicegerent, who has the duty to protect human life as a form of devotion to Him. Therefore, applying Islamic medical ethics is expected to help create professional, humane, and morally guided healthcare services.